Multifaceted profiling of virus-specific CD8 T cells reveals distinct immune signatures against cytomegalovirus infection states during pregnancy - Ayumi Taguchi; Fumi Misumi; Shunsuke Teraguchi; Takeshi Nagamatsu; Shuhei Sakakibara; Tomohiro Otani; Mari Ichinose; David Priest; Kazuki Nakajima; Junko Nakamura; Ryoko Sawada; Tatsuo Suzutani; et al. (iScience)
Summary: Anti-cytomegalovirus (CMV) serological testing, including the IgG avidity index (AI), is used to assess CMV infection phases during pregnancy. However, little is known about anti-CMV cellular immunity during pregnancy, particularly its relation to serological diagnosis. Herein, using MHC-dextramer single-cell RNA sequencing and flow cytometry, we characterized IE1 and pp65 CMV-antigen specific CD8 T cells from pregnant women with different anti-CMV serological patterns, including IgG+IgM+/AI-low, IgG+IgM+/AI-high, and IgG+IgM−. In IgG+IgM+/AI-low and IgG+IgM+/AI-high specimens, CMV-specific T cells consisted largely of effectors, with a minor but characteristic proportion of memory T cells, including HLA-DR-positive memory precursors and granzyme K-high memory cells reactive to IE1. Conversely, IgG+IgM− cases had a distinctive expansion of pp65-specific terminally differentiated T effector memory with a signature of convergent clonal selection. Our findings revealed that different CMV infection phases have characteristic patterns of CD8 cell phenotype and antigen recognition, potentially offering a new approach for assessing congenital infection risk.